Popularity versus quality in TikTok educational videos on congenital nasolacrimal duct obstruction - Zhu, Manhui; Xi, Wenqun; Xu, Lin; Tu, Yuanyuan; Zhao, Jialuo; Guo, Yingxin; Zhang, Zhe; Zhu, Zhentao; Jiang, Ligang (Frontiers in Medicine, 2026)
BackgroundCongenital nasolacrimal duct obstruction is a common ocular condition in early infancy and may lead to neonatal dacryocystitis or severe infection if not treated promptly. Short-video platforms such as TikTok are used by young parents to obtain health information, but the quality of related videos remains unclear. This study evaluated the quality of TikTok videos on congenital nasolacrimal duct obstruction and its association with uploader type and user engagement.MethodsWe conducted a cross-sectional review of TikTok videos retrieved with predefined keywords. We included 108 videos, classified by uploader type, and extracted characteristics, engagement metrics, and coverage of six content domains. Two attending ophthalmologists independently rated each video using DISCERN, the Global Quality Score, and the Patient Education Materials Assessment Tool for Audiovisual Materials. Group differences and Spearman correlations were analyzed.ResultsAmong 108 videos, 62 (57.4%) were uploaded by medical professionals and 18 (16.7%) by non-Profit organizations, with a median duration of 48.5 s and median numbers of likes, comments, favorites and shares of 68, 8, 13, and 24, respectively. Videos uploaded by non-Profit organizations and medical professionals achieved substantially higher DISCERN scores (about 59.22 and 50.00 vs. 37.50 and 19.40), Global Quality Scores (median 4.5 and 4.0 vs. 3.0 and 1.0), and Patient Education Materials Assessment Tool for Audiovisual Materials understandability (median 92.31 and 84.62% vs. 73.08 and 53.85%) and actionability (both 75.00% vs. 66.67 and 50.00%) than those uploaded by non-Medical individuals and for-profit organizations (all P < 0.001). Spearman analysis found no significant correlations between overall quality scores and engagement, but duration correlated weakly with some selected quality indicators (r = 0.17–0.21, P < 0.05).ConclusionTikTok videos on congenital nasolacrimal duct obstruction show marked heterogeneity in content completeness and educational quality, largely determined by uploader type. Non-Profit organizations and medical professionals produce more reliable, understandable, and actionable videos, but these are not consistently more popular than lower-quality content. Clinicians and institutions should develop guideline-concordant short videos and direct parents toward trustworthy channels, while platforms consider mechanisms to highlight professionally verified pediatric eye-health information.